371 Sentinel lymph nodeidentification with patent blue dye in gynecologic oncology. Initial experience. (18th September 2019) - Castillo, R; Perfetti, W; Hidalgo, F; Gimenez, M; Payares, E; Borges, A
Abstract : Instituto de Oncologia Dr. Miguel Perez Carreno, Ginecologia Oncologica, Naguanagua, Venezuela Objectives: The use of Sentinel Lymph Node (SLN) biopsy in oncological gynecology is increasing every day and there are multiple studies that demonstrate its effectiveness. This study aims to evaluate the effectiveness of the sentinel lymph node in early stages for cervical, endometrial and vulvar cancer. Methods: A prospective study was conducted in early stage patients with endometrial, cervix and vulvar cancer, where the sentinel lymph node technique with patent blue dye followed by completed lymphadenectomy was used. Results: The sample was represented by 20 patients, 10 (50%) Endometrial adenocarcinoma, 8 (40%) Squamous cervical cancer, 2 (10%) Squamous Vulvar cancer. After the identification of the sentinel node, pelvic lymphadenectomy was performed in patients with endometrial adenocarcinoma, obtaining an average of 6 (± 0.9) left lymph nodes and 6 (± 1.4) right lymph nodes, in cervical cancer 7 (± 2.6) left lymph nodes and 7 (± 3.3) right lymph nodes an vulvar cancer superficial inguinal lymphadenectomy was performed, obtaining 15 (± 9.1) left lymph nodes and 14 (± 5.6) right lymph nodes. Among patients with endometrial adenocarcinoma, one patient had a negative sentinel lymph node and definitive biopsy reported micrometastasis. Sentinel node technique had a positive predictive value 100% and negative predictive value 94%. Conclusions: In this study the sentinel node showed high sensitivity and specificity. Although the effectiveness has been proven throughout the world, it is important to make a learning curve in each center.